2006
DOI: 10.1007/s00299-006-0240-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the hyp-1 gene in early stages of development of Hypericum perforatum L.

Abstract: Level of expression of the hyp-1 gene encoding for the phenolic coupling protein which is assumed to be involved in conversion of emodin to hypericin in vitro was compared in different organs of Hypericum perforatum seedlings in early stage of development in order to find out the sites of hypericin biosynthesis. Hypericins are accumulated in multicellular dark glands distributed on the aerial parts of H. perforatum, however, the site of the final stages of their biosynthesis remains unclear. In order to verify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 23 publications
2
30
3
Order By: Relevance
“…This is the first study of the presence of Hyp-1 protein in H. perforatum. The role of Hyp-1 in the biosynthesis of hypericins is not fully understood [11,21]. However, our results of the presence of Hyp-1 in H. perforatum leaves at different developmental stages are in agreement with the report of accumulation of hypericins in the plant.…”
Section: Immunoblotting Analysis Of Hyp-1supporting
confidence: 95%
“…This is the first study of the presence of Hyp-1 protein in H. perforatum. The role of Hyp-1 in the biosynthesis of hypericins is not fully understood [11,21]. However, our results of the presence of Hyp-1 in H. perforatum leaves at different developmental stages are in agreement with the report of accumulation of hypericins in the plant.…”
Section: Immunoblotting Analysis Of Hyp-1supporting
confidence: 95%
“…and HpPKS2 genes with the contents of major bioactive compounds in different H. perforatum tissues Hypericins and pseudohypericins are shown to accumulate into multicellular dark glands found primarily on leaf margins and flowers of H. perforatum (Briskin and Gawienowski, 2001;Onelli et al, 2002;Zobayed et al, 2006;Košuth et al, 2007). The stems usually contain fewer dark glands, and glands cannot be found from the roots of H. perforatum (Košuth et al, 2007).…”
Section: Comparison Of Expression Of Hppks1mentioning
confidence: 98%
“…More recently, however, it was revealed that the hyp-1 gene might not have a function in hypericin biosynthesis. We studied the expression of the hyp-1 gene in different organs of H. perforatum seedlings in early stages of development, which was believed to indicate the location of the sites of biosynthesis of hypericin [18]. We revealed that the sites of biogenesis and accumulation of hypericin in Hypericum plants were independent of the expression of the hyp-1 gene at the transcript level.…”
Section: Introductionmentioning
confidence: 97%